Computational Microfluidics for Geosciences - Soulaine, Cyprien; Maes, Julien; Roman, Sophie (Frontiers in Water, 2021)
Computational microfluidics for geosciences is the third leg of the scientific strategy that includes microfluidic experiments and high-resolution imaging for deciphering coupled processes in geological porous media. This modeling approach solves the fundamental equations of continuum mechanics in the exact geometry of porous materials. Computational microfluidics intends to complement and augment laboratory experiments. Although the field is still in its infancy, the recent progress in modeling multiphase flow and reactive transport at the pore-scale has shed new light on the coupled mechanisms occurring in geological porous media already. In this paper, we review the state-of-the-art computational microfluidics for geosciences, the open challenges, and the future trends.